Modern Methods of Working in Cooperation with Students in the Educational Process - Isakhonovich, Shodmonov Bakhtiorkhoja (Researchparks Publishing, 2023)
This article presents information about the role and importance of collaborative teaching technology, the current problems of reshaping and implementing all modern methods of working with students based on national interests, and reforms in the field of education.